Cordyceps locustiphila (Hypocreales: Cordycipitaceae) infecting the grasshopper pest Tropidacris collaris (Orthoptera: Acridoidea: Romaleidae) - Pelizza, Sebastian A. (2018)
Cordyceps locustiphila is described, illustrated, and compared with a previous finding. This species was collected infecting Tropidacris collaris in the Yabotí biosphere reserve, Misiones province, Argentina. Until now, this entomopathogenic fungus has not been reported affecting T. collaris, and it is the first report for Argentina. From the cordyceps-like stromata of C. locustiphila it was possible to isolate for the first time the acremonium-like anamorph of this fungus. The identity of both, anamorph and teleomorph, was determined by morphological and molecular taxonomic studies, which challenges the recent new combination into Beauveria